2020
DOI: 10.1016/j.jad.2020.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive performance of repeated versus single intravenous subanesthetic ketamine in treatment resistant depression

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 44 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…Importantly, clinical status moderates the extent to which an individual will experience changes in cognition following ketamine exposure [ 19 ]. Single and repeated ketamine administration exerts pro-cognitive effects in preclinical models of depressive-like behavior [ 98 101 ] and in patients with treatment-resistant major depression [ 6 , 21 , 23 , 40 ], especially those suffering from comorbid anxiety [ 40 ]. The cognition-enhancing properties of ketamine observed in patients suffering from depression may be explained by the fact that many of these patients show baseline cognitive deficits [ 24 , 25 ] and may be related at least in part to its antidepressant actions [ 23 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, clinical status moderates the extent to which an individual will experience changes in cognition following ketamine exposure [ 19 ]. Single and repeated ketamine administration exerts pro-cognitive effects in preclinical models of depressive-like behavior [ 98 101 ] and in patients with treatment-resistant major depression [ 6 , 21 , 23 , 40 ], especially those suffering from comorbid anxiety [ 40 ]. The cognition-enhancing properties of ketamine observed in patients suffering from depression may be explained by the fact that many of these patients show baseline cognitive deficits [ 24 , 25 ] and may be related at least in part to its antidepressant actions [ 23 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, six infusions of ( R,S )-ketamine (0.5 mg/kg) significantly ameliorated cognitive impairment, as measured by processing speed, in patients with treatment-resistant MDD or BD [ 168 170 ]. A recent systematic review revealed that ( R,S )-ketamine infusion showed significant improvements in cognitive impairment in patients with treatment-resistant MDD, although ( R,S )-ketamine did not worsen cognitive function in depressed patients [ 171 ], as had been observed in healthy controls [ 166 , 167 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one double-blind, randomized, controlled clinical trial of 62 individuals with TRD, ketamine had no deleterious effect on cognitive functioning; in addition, poor processing speed at baseline was associated with improved antidepressant response to ketamine [ 53 ]. In another study of 43 individuals with TRD randomized to receive one or six ketamine infusions, researchers reported some improvements in short-term neurocognitive function, particularly in the domains of processing speed, set shifting, and spatial working memory [ 54 ]. Finally, a recent retrospective study of 68 individuals with TRD found that ketamine had pro-cognitive effects, including depression-independent improvements in working memory as measured by the Trail Making Test [ 55 ].…”
Section: Ketamine For Other Psychiatric Indicationsmentioning
confidence: 99%